Pemanfaatan Pojok Baca dalam Meningkatkan Minat Baca Siswa SDN Puro Pakualaman 1 - Cahaya Safitri Ningsih; Ana Fitrotun Nisa (Jurnal Pendidikan Dasar, 2023)
Abstract: The purpose of this study was to increase students' interest in reading in grade II at SDN Puro Pakualaman 1 by using a reading corner.This study used a qualitative descriptive method. Data collection techniques were observation and interviews which then produced documentation. The research subjects were class II students at SDN Puro Pakualaman 1. The results of his research were that there was a reading corner, students' interest in reading increased. The use of reading corners in increasing reading interest among others: utilizing the book collection for the school literacy movement 15 minutes before learning, utilizing the reading corner as material for student discussion, and utilizing the reading corner to fill students free timeKeywords: reading corner,interest read Abstrak: Tujuan penelitian ini untuk meningkatkan minat membaca siswa kelas II di SDN Puro Pakualaman 1 dengan pemanfaatan pojok baca. Penelitian ini menggunakan metode deskriptif kualitatif.Teknik pengumpulan data dengan observasi dan wawancara yang kemudian menghasilkan dokumentasi.Subjek penelitian adalah siswa kelas II SDN Puro Pakualaman 1. Hasil penelitianya dengan adanya pojok baca, minat membaca siswa meningkat.Pemanfaatan pojok baca dalam meningkatan minat membaca antara lain : memanfaatkan koleksi buku untuk gerakan literasi sekolah 15 menit sebelum pembelajaran, memanfaatkan pojok baca sebagai bahan diskusi siswa, dan memanfaatkan pojok baca untu mengisi waktu luang siswaKata Kunci: pojok baca, minat baca